2004
DOI: 10.1007/s00125-004-1452-1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal oral administration of DiaPep277, combined with hydrolysed casein diet, protects against Type 1 diabetes in BB-DP rats. An experimental study

Abstract: Aims/hypothesis. Environmental factors such as diet and bacterial antigens play an important role in the onset of Type 1 diabetes. Different self-antigens are suggested to play a role in the development of diabetes. Antibodies against the 60-kDa heat shock protein 60, which have a high homology to bacterial heat shock protein 65, have been found in the circulation at the onset of diabetes in humans and in pre-diabetic NOD-mice. One of the immunodominant epitopes in autoimmune diabetes is p277, a specific pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The increasing prevalence of food allergies in Western societies has led to the hypothesis that increased hygienic conditions throughout life can disturb normal tolerance induction to otherwise harmless food proteins and other (inhaled) antigens. Previous studies have shown that modulation of antigen exposure early in life can change the diabetes incidence in BB-DP rats [5,6]. Furthermore, the antistaphylococcal drug fusidin was able to decrease the diabetes incidence in BB-DP rats [7].…”
Section: Introductionmentioning
confidence: 92%
“…The increasing prevalence of food allergies in Western societies has led to the hypothesis that increased hygienic conditions throughout life can disturb normal tolerance induction to otherwise harmless food proteins and other (inhaled) antigens. Previous studies have shown that modulation of antigen exposure early in life can change the diabetes incidence in BB-DP rats [5,6]. Furthermore, the antistaphylococcal drug fusidin was able to decrease the diabetes incidence in BB-DP rats [7].…”
Section: Introductionmentioning
confidence: 92%
“…In BBDP rats, gliadin exposure is accompanied by increased intestinal permeability (115) and zonulin release (168,173), presumably allowing food antigens to come in contact with the underlying lamina propria. Feeding NOD mice and BBDP rats a gluten-free hydrolyzed casein diet resulted in a delay and reduction of T1D development (27,28,144,167). Interestingly, in these animal models of T1D, the moment of exposure to wheat proteins was shown to be important for the development of T1D.…”
Section: Zonulin and Intestinal Barrier Functionmentioning
confidence: 99%
“…Furthermore, previous findings suggest that immunomodulators of the neonatal gut immune system play a particular role in controlling diabetes development [19,20]. According to the hygiene hypothesis, decreased bacterial exposure in early life leads to defective Treg cell induction, and is thus responsible for an autoimmune initiation of inflammatory cytokine production [2,21,22].…”
Section: Introductionmentioning
confidence: 99%